Paradigms underlying the "Synod on synodality" and possible difficulties in their reception - Godlewski, Karol (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
"Synod" is an ancient and venerable word in the Tradition of the Church, whose meaning evokes the deepest content of Revelation. It is composed of the preposition "syn" and the noun "hodos", which together give the Greek word "synhodos", meaning the path ("hodos") along which the People of God walk together ("syn"). Among the many synods at the level of the universal Church convened by recent popes, a special place is occupied by the ongoing Synod on synodality, started in 2021 at the will of Pope Francis. It is the fruit of the urgency that comes from the question that bothers the people of the Church: how today, at various levels of the Church, from the local to the universal, is this "walking together" realized, which allows the Church, in accordance with the mission entrusted to it, to proclaim the Good The news, and what actions the Holy Spirit himself invites him to take aimed at the growth of the Church as a synodal Church. Both at the stage of preparation for the synod and during its duration, both from the documents and statements of the Holy Father and people responsible for managing the work of the synod, as well as from observing the priorities that guide this synodal process, several fundamental paradigms underlying the Synod on synodality. This article will discuss three of them: the value of every person, discernment and the missionary nature of the Church. Attention will also be paid to both potential and current difficulties in the reception of these paradigms and - as a consequence - the entire synodal process in the Church.